Bridging the Digital Divide: Corporate-Rural Partnerships in MSMEs Transformation through Shopee Center - Muhamad Ihsan Pahlefi; Angga Gumilar; Yogi Sugiarto Maulana (International Journal of Economics and Management Research, 2024)
This qualitative study investigates the corporate e-commerce strategy implemented by Shopee through its Shopee Center program to empower Micro, Small, and Medium Enterprises (MSMEs) in Bangunharja Village, Indonesia. Employing a descriptive case study methodology, the research engaged 11 key informants comprising Shopee representatives, local MSME actors, and BUMDES (Village-Owned Enterprise) leadership. Data collection incorporated in-depth interviews, participatory observation, and documentary analysis, with subsequent examination following the interactive model of Miles and Huberman. The findings demonstrate that Shopee's strategic approach effectively catalyzed initial digital adoption among rural MSMEs through multifaceted interventions: comprehensive digital literacy training, enhanced internet infrastructure via affordable WiFi partnerships, and robust collaboration with local institutions. Notably, the program facilitated product innovation and market expansion for various MSMEs, enabling traditional businesses to access digital marketplaces. However, the research identifies persistent challenges including declining participation rates over time, ongoing digital literacy gaps, and infrastructural limitations in internet connectivity. The study concludes that while corporate-led initiatives significantly advance digital inclusion, sustainable transformation necessitates continuous program adaptation, advanced skill development modules, and strengthened multi-stakeholder cooperation to address systemic barriers in rural digital ecosystems.